Intervensi Guru terhadap Kemandirian dalam Perspektif Psikopedagogis - Elan, Elan; Fathy, Manzilatul (UIN Sultan Maulana Hasanudin Banten, 2025)
Independence is an important part of early childhood development that needs to be stimulated early on. Independent children are able to make simple decisions, are responsible for themselves, and are able to manage their emotions without excessive dependence on adults. In the process of forming this independence, teachers have a strategic role, not only as educators but also as mentors and role models. This study aims to describe how teachers intervene in forming early childhood independence from a psychopedagogical perspective. This study uses a library research method, namely by reviewing various theories and relevant previous research findings. The results of the study show that teachers can form children's independence through a psychopedagogical approach such as giving simple responsibilities, positive habits, verbal reinforcement, and implementing scaffolding. Teachers also need to create an emotionally safe learning atmosphere and support children's exploration. As a figure who is close to the child, teachers must be able to present a learning process that does not suppress, but rather fosters. Thus, early childhood independence can grow through appropriate and sustainable interventions, especially if also supported by a consistent home environment.